2019
DOI: 10.1002/rob.21908
|View full text |Cite
|
Sign up to set email alerts
|

A path planning and path‐following control framework for a general 2‐trailer with a car‐like tractor

Abstract: Maneuvering a general 2‐trailer with a car‐like tractor in backward motion is a task that requires a significant skill to master and is unarguably one of the most complicated tasks a truck driver has to perform. This paper presents a path planning and path‐following control solution that can be used to automatically plan and execute difficult parking and obstacle avoidance maneuvers by combining backward and forward motion. A lattice‐based path planning framework is developed in order to generate kinematically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 69 publications
1
89
0
Order By: Relevance
“…After the discretization has been selected, the connectivity in the graph is chosen by selecting which neighboring states to connect. Finally, the set of motion primitives P is constructed by computing N m motion segments (for example using an OCP solver as in [20], [5]) needed to connect the neighboring states, without considering obstacles. A motion primitive m ∈ P is defined as…”
Section: B Lattice-based Path Plannermentioning
confidence: 99%
See 1 more Smart Citation
“…After the discretization has been selected, the connectivity in the graph is chosen by selecting which neighboring states to connect. Finally, the set of motion primitives P is constructed by computing N m motion segments (for example using an OCP solver as in [20], [5]) needed to connect the neighboring states, without considering obstacles. A motion primitive m ∈ P is defined as…”
Section: B Lattice-based Path Plannermentioning
confidence: 99%
“…In this paper, optimal path planning is defined as the problem of finding a feasible and collision-free path from the vehicle initial state to a desired goal state, while a specified performance measure is minimized. This path is then intended to be used as a reference for a path-following controller, such as the ones described in [2], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a more reliable convergence for the nlp solver, we have observed that it can be beneficial to compute the motion primitives for backward motion from the goal state to the initial state in forward motion for which the system is stable. Since the truck and trailer system is on the form of Lemma 1 in [52], it is possible, according to Theorem 1 in [52], to obtain an optimal backward motion (x * t,b (τ ), u * b (τ )), τ ∈ [0, T ] that brings the system from x start to x final , from the optimal forward motion (x * t,f (t), u * f (t)), t ∈ [0, T ]. This can be achieved by the state and control transformation: 15) where the optimal forward motion is obtained by solving the motion primitive ocp (4.2) from x final to x start .…”
Section: Vehicle Modelsmentioning
confidence: 99%
“…Note that it is only the steering angle rate ω and the velocity v 1 that change signs, while the other states and controls are fully time-reversed. For a detailed description of this property, the reader is referred to [52].…”
Section: Vehicle Modelsmentioning
confidence: 99%
“…For road vehicles, several path/motion planning strategies are demonstrated ( Karaman and Frazzoli, 2011 ). In their recent studies, Ljungqvist et al (2019) and Cirillo (2017) demonstrated the use of the Lattice-based method for path/motion planning. In both works where the focus was path planning, the algorithms developed were tested on real vehicles.…”
Section: Introductionmentioning
confidence: 99%